2021
DOI: 10.1111/ijlh.13663
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of Abbott Alinity hq extended red blood cell parameters in differentiating β‐thalassemia trait and iron deficiency anemia

Abstract: Introduction:The objective of the study was to evaluate the performance of the Abbott Alinity hq advanced multi angle polarized scatter separation (MAPSS TM )based optical RBC technology, for the differentiation between iron deficiency anemia (IDA) and β-thalassemia carrier status.Methods: Four hundred and sixty-four samples were analyzed. 228 were healthy controls, 30 were β-thalassemia carriers, and 40 were IDA. Receiver operating characteristics analysis evaluated the performance of red cell parameters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For instance, a previous study suggests that the Mentzer index (MCV/RBC) is able to differentiate between patients with β‐TT and IDA with a sensitivity and specificity of 91% and 83%, respectively, in pregnant women 6 . Another study evaluated the capability of optical RBC technology for discriminating patients with β‐TT and IDA and revealed that the RBC concentration has the best discriminative value with an AUC of 0.963, followed by the RBC distribution width in the size distribution with an AUC of 0.960 and the RBC distribution width coefficient of variation with an AUC of 0.924 34 . Moreover, it has also been proposed that the RBC distribution width index (MCV/RBC × RBC distribution width) has better distinguishing ability between β‐TT and IDA than other parameters, including RBC count and RBC distribution width, in children from Iraq 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a previous study suggests that the Mentzer index (MCV/RBC) is able to differentiate between patients with β‐TT and IDA with a sensitivity and specificity of 91% and 83%, respectively, in pregnant women 6 . Another study evaluated the capability of optical RBC technology for discriminating patients with β‐TT and IDA and revealed that the RBC concentration has the best discriminative value with an AUC of 0.963, followed by the RBC distribution width in the size distribution with an AUC of 0.960 and the RBC distribution width coefficient of variation with an AUC of 0.924 34 . Moreover, it has also been proposed that the RBC distribution width index (MCV/RBC × RBC distribution width) has better distinguishing ability between β‐TT and IDA than other parameters, including RBC count and RBC distribution width, in children from Iraq 35 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Another study evaluated the capability of optical RBC technology for discriminating patients with β-TT and IDA and revealed that the RBC concentration has the best discriminative value with an AUC of 0.963, followed by the RBC distribution width in the size distribution with an AUC of 0.960 and the RBC distribution width coefficient of variation with an AUC of 0.924. 34 Moreover, it has also been proposed that the RBC distribution width index (MCV/RBC × RBC distribution width) has better distinguishing ability between β-TT and IDA than other parameters, including RBC count and RBC distribution width, in children from Iraq. 35 However, the conditions of TT and parameters of RBC According to previous studies, α-TT and β-TT are prevalent in Fujian Province.…”
Section: Discussionmentioning
confidence: 99%